Everyday heaven : journeys beyond the stereotypes of autism - Williams, Donna, 1963- (Jessica Kingsley, 2004)
Everyday Heaven is the much-awaited fourth installment in Donna Williams' series of best-selling autobiographies about her life with autism. A humorous, riveting, roller-coaster of a book, Everyday Heaven covers the monumental nine years from the time Ian left their accidental, 'autistic marriage', to Donna's candid, funny, often bumbling explorations of sexuality and orientation, the challenge of coming to terms with the sudden deaths of those closest to her and finally knowing what life was like without the invisible cage of her 'Exposure Anxiety'. Described as enthralling, deeply moving and.